Evolution, plasticity and evolving plasticity of phenology in the tree species Alnus glutinosa. (17th November 2015) - De Kort, H.; Vander Mijnsbrugge, K.; Vandepitte, K.; Mergeay, J.; Ovaskainen, O.; Honnay, O.
Abstract: Both traits and the plasticity of these traits are subject to evolutionary change and therefore affect the long‐term persistence of populations and their role in local communities. We subjected clones from 12 different populations of Alnus glutinosa, located along a latitudinal gradient, to two different temperature treatments, to disentangle the distribution of genetic variation in timing of bud burst and bud burst plasticity within and among genotypes, populations, and regions. We calculated heritability and evolvability estimates for bud burst and bud burst plasticity and assessed the influence of divergent selection relative to neutral drift. We observed higher levels of heritability and evolvability for bud burst than for its plasticity, whereas the total phenological heritability and evolvability (i.e. combining timing of bud burst and bud burst plasticity) suggest substantial evolutionary potential with respect to phenology. Earlier bud burst was observed for the low‐latitudinal populations than for the populations from higher latitudes, whereas the high‐latitudinal populations did not show the expected delayed bud burst. This countergradient variation can be due to evolution towards increased phenological plasticity at higher latitudes. However, because we found little evidence for adaptive differences in phenological plasticity across the latitudinal gradient, we suggest differential frost tolerance as the most likely explanation for the observed phenological patterns in A. glutinosa .